DEPRESSION IN FREDDIE MERCURYâ€™S SONG LYRICS: â€œBOHEMIAN RHAPSODYâ€, â€œSOMEBODY TO LOVEâ€ AND â€œLOVE OF MY LIFEâ€ - Risqullah, Zaki (Faculty of Letters, Dr. Soetomo University, 2018)
This research deals with Depression in Freddie Mercuryâ€™s song lyrics. It is focused on the symptomsÂ of depression implied in the song lyrics entitled â€œBohemian Rhapsodyâ€, â€œLove of My Lifeâ€, and â€œSomebody to Loveâ€. The objectives of the study are to find out the poetic devices in Freddie Mercuryâ€™s song lyrics entitled â€œBohemian Rhapsodyâ€, â€œLove of My Lifeâ€, and â€œSomebody to Loveâ€ and to describe the depression symptoms portrayed in Freddie Mercuryâ€™s song lyrics entitled â€œBohemian Rhapsodyâ€, â€œLove of My Lifeâ€, and â€œSomebody to Loveâ€. The theories used to analyse the data are Aaron T. Beckâ€™s depression and William Wordsworthâ€™s theory of poetry. Pragmatic approach and qualitative research design were applied in conducting the study. The techniques ofÂ data collection and analysis covered close reading and content analysis. Findings show that â€œBohemian Rhapsodyâ€ makes use of hyperbole, metonymy, situational irony, antithesis, repetition, and allusion as poetic devices. The depression symptoms undergone by the speaker of the song lyrics entitled â€œBohemian Rhapsodyâ€ cover Low Self-Evaluation., Loss of Emotional Attachments, and Negative Feelings toward Self. The second song lyrics entitled â€œSomeone to Loveâ€ employ repetition, hyperbole, and personification. The speaker of the song lyrics suffers from Reduction in Gratification. The song lyrics entitled â€œLove of My Lifeâ€ make use of hyperbole, repetition, personification, and symbol as the poetic devices. The character â€˜Iâ€™, in the song lyrics, suffer from Dejected Mood. Â